What is Node? - McLaughlin, Brett (O'Reilly, 2011)
"Node.js. It's the latest in a long line of 'Are you cool enough to use me?' programming languages, APIs, and toolkits. In that sense, it lands squarely in the tradition of Rails, and Ajax, and Hadoop, and even to some degree iPhone programming and HTML5. Get up to speed on Node with this concise overview."--Resource description page.